(3CUhd GdHROhis - (3CHh GdMSf Ydj Hf eMeO GdHROhis; (3GdHROhj , Ydj Hf eMeO Hf GdMSjf Hf YHO GdcQje, aNQ GdGSdGe CHh GdMSf,J (B482 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdYde fhYGf Yde GdJhMjO hGdUaGJ hYde GdTQGFY hGdCMcGe s
(3BNQgG (B:s
(3hPdc eKd JfGhd GdeMXhQ GdEMQGe Yf VQhQI GdeMQe Cfg jQNU dg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B328 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B192s
Keywords: (3CUhd Gdabgs